Medical education and law: withholding/withdrawing treatment from adults without capacity. Issue 6 (June 2015) - Parker, M; Willmott, L; White, B; Williams, G; Cartwright, C
Abstract Background Law is increasingly involved in clinical practice, particularly at the end of life, but undergraduate and postgraduate education in this area remains unsystematic. We hypothesised that attitudes to and knowledge of the law governing withholding/withdrawing life‐sustaining treatment from adults without capacity (the WWLST law) would vary and demonstrate deficiencies among medical specialists. Aims We investigated perspectives, knowledge and training of medical specialists in the three largest (populations and medical workforces) Australian states, concerning the WWLST law. Methods Following expert legal review, specialist focus groups, pre‐testing and piloting in each state, seven specialties involved with end‐of‐life care were surveyed, with a variety of statistical analyses applied to the responses. Results Respondents supported the need to know and follow the law. There were mixed views about its helpfulness in medical decision‐making. Over half the respondents conceded poor knowledge of the law; this was mirrored by critical gaps in knowledge that varied by specialty. There were relatively low but increasing rates of education from the undergraduate to continuing professional development (CPD) stages. Mean knowledge score did not vary significantly according to undergraduate or immediate postgraduate training, but CPD training, particularly if recent, resulted in greater knowledge. Case‐based workshops were the preferred CPD instruction method. Conclusions Teaching of current and evolving law should be strengthened across all stages of medical education. This should improve understanding of the role of law, ameliorate ambivalence towards the law and contribute to more informed deliberation about end‐of‐life issues with patients and families.